Factors Driving Readmissions in Tibia and Femur Fractures. (10th March 2015) - Chern, Alexander; Greenberg, Sarah E.; Thakore, Rachel V.; Sathiyakumar, Vasanth; Obremskey, William T.; Sethi, Manish K.
Abstract : As the American healthcare system shifts towards bundled payments, readmissions will become a measure of healthcare quality. The purpose of this study was to characterize readmission trends and factors influencing readmission in patients with diaphyseal femur and tibia fractures. Through a retrospective chart review, all patients who presented to a level 1 trauma center from 2004 to 2006 were evaluated. By using current procedural terminology codes, 1, 040 patients with diaphyseal tibia or femur fractures fixed by IMN were identified. 645 patients were included for analysis. 30-day, 60-day, and 90-day readmission rates were compared with fracture type, reason for readmission, and basic demographic information. The 60-day readmission rate for open tibia fractures (14.8%) was significantly higher than the 60-day readmission rate for closed tibia fractures (8.0%) (p = 0.037 ). When comparing reasons for 60-day readmissions, 50% of closed fractures were readmitted due to infection, while the other 50% needed additional surgery. 91.7% of open fractures readmitted in 60 days were due to infection. In a bundled payment system, orthopedic trauma must gain insight into drivers of readmission to identify those at risk for readmission and design effective healthcare plans for these patients.